IMPROVING SCIENCE LEARNING OUTCOMES BY APPLYING THE GUIDED DISCOVERY LEARNING MODEL - Putri Anggraini; Fahmi Fahmi; Yudha Irhasyuarna (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2024)
The selection of the right model for learning will affect the learning outcomes of students' cognitive abilities. Therefore, a study was conducted that aims to improve students' learning outcomes using the guided discovery learning model. This classroom action research aims to describe science learning with the guided discovery learning model to improve learning outcomes. This study was conducted in three cycles. Each cycle consists of planning, implementation, observation, and reflection. Cognitive learning outcome data were obtained from essay tests. The results of the study showed an increase in the learning outcomes of class VII D students of SMPN 1 Rantau Badauh after the application of the guided discovery learning model on the topic of heat.Keywords: Learning outcomes, guided discovery learning model. Pemilihan model yang tepat untuk pembelajaran akan berpengaruh terhadap hasil belajar kemampuan kognitif peserta didik. Maka dari itu, dilakukan penelitian yang bertujuan untuk meningkatkan hasil belajar peserta didik dengan menggunakan model guided discovery learning. Penelitian tindakan kelas ini bertujuan untuk mendeskripsikan pembelajaran sains dengan model guided discovery learning untuk meningkatkan hasil belajar. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Data hasil belajar kognitif diperoleh dari tes essay. Hasil penelitian menunjukkan ada peningkatan hasil belajar siswa kelas VII D SMPN 1 Rantau Badauh setelah penerapan model pembelajaran guided discovery learning pada pokok bahasan kalor.Kata kunci: Hasil belajar, model guided discovery learning